Seemingly inclusive liminal legality: the fragility and illegality production of Colombia's legalization programmes for Venezuelan migrants. - Del Real, Deisy (Journal of Ethnic & Migration Studies, 2022)
Venezuelans constitute the second largest displaced population globally. Most Venezuelans move to Colombia, where the government incorporates them through administrative legalisation programmes. While the international community has praised Colombia's governmental response, this article demonstrates that these programmes provide Venezuelans with liminal legality. Existing liminal legality research indicates that recipients are highly aware of the fragility of their legal status because they live in hostile political contexts with complicated legalisation procedures. However, the present article argues that liminal legality in inclusive political contexts such as Colombia—with straightforward application procedures, pro-immigrant political discourse, and weak immigration enforcement—hide this legal status' fragility and illegality production features. Empirically, the study draws on in-depth interviews with Venezuelan migrants in Bogotá, D.C. Findings show that most liminal legality recipients want to reside legally in Colombia and experience their legal status with a sense of state protection. Though, their sense of security inhibits their efforts to acquire legal permanent residency. Conversely, undocumented Venezuelans tend to have the fewest resources before emigrating, cannot meet the liminal legality requirements, and experience all forms of legality as unattainable. Broadly, governments who seek to legalise migrants need to include direct pathways to citizenship and lower the legal residency requirements.